Courage in Moment : The civil Rights struggle, 19961-1964 - Paul Dickson (dover publication, 2012)
While many mainstream Southern newspapers ignored the burgeoning civil rights movement in the early 1960s, student journalists from the University of North Carolina at Chapel Hill bravely ventured out every day to document protest marches and other demonstrations in their town. One of those North Carolina students, Jim Wallace, took these dramatic photographs primarily during the watershed year of 1963. These are powerful scenes from a new American revolution, ranging from peaceful sit-ins and protest marches to tense and dramatic confrontations with the authorities, to disturbing images from a chilling Ku Klux Klan rally which Wallace encountered during this time. Caught up in documenting the struggle, Wallace went on to photograph the pivotal 1963 March on Washington, and images from that memorable event are also included here. In this engrossing account, Jim Wallace recalls those dramatic days in detail and offers insightful reflections on these 100 black-and-white images and his memories of the people and events they portray. Many of these pictures have never been seen before. Text and images combine to create a vital document of the American civil rights movement.